Achievement Matters : External Peer Review of Accounting Learning Standards : Final Report of the External Evaluation. - Boyle, Patrick (Office for Learning and Teaching, 2014)
Evaluation report from a project that followed on from the establishment of the Australian national accounting learning standards for bachelor and coursework master degrees. The project involved 35 accounting academics from 17 institutions including universities, private and TAFE providers, and collaborated with accounting professional bodies and practitioners. Using assessment tasks and sample student work, the project developed a model external calibration process to achieve shared understandings among participants across all the accounting learning standards. Following calibration, random samples of student work were anonymously assessed by the calibrated peer reviewers benchmarked against the accounting learning standards. The project demonstrated that external calibration was a rich source of professional development around assessment for participating academics and improved the reliability of judgements. The project also demonstrated that following external calibration, double-blind peer review can provide useful external assurance of learning data to support improvements.